Field study on weeds incidence in rapeseed (Brassica campestris L.). (Journal of Bio-Science, 2019)
A survey was conducted to highlight the weed flora infesting rapeseed in the experimental field of Rajshahi University. Frequency (F), density (D), abundance (A), relative frequency (RF), relative density (RD), relative abundance (RA) and importance value index (IVI %) of weeds were calculated in rapeseed field. The objective of the study was to study the weeds and their quantitative characters. Weed infestation was studied in three rapeseed varieties (BARI Sharisha 14, BINA Sharisha 5 and 6). The weed population was studied using quadrat. The species which had 100% frequency values were Cyperus rotundus, Cynodon dactylon, Ammania baccifera, Echinochloa crusgalli and Leucas lavendulifolia. Other species had 50% or less than 50% frequency values. The highest frequency, density, abundance and importance value index were exhibited by Cyperus rotundus.J. bio-sci. 26: 01-06, 2018